An endergonic synthesis of single Sondheimer–Wong diyne by local probe chemistry - Kawai, Shigeki (2023)
Recent advances in scanning probe microscopy on surface enable not only direct observation of molecular structures but also local probe reactions, in which unstable short-lived products have been synthesized and analyzed. Now, an endergonic reaction to synthesize a single Sondheimer–Wong diyne from 6,13-dibromopentaleno[1,2-b:4,5-b’]dinaphthalene by local probe chemistry on a ultra-thin film of NaCl formed on a Cu(111) surface at 4.3 K is presented. The structures of the precursor, two intermediates, and the final product were directly identified by the differential conductance imaging with a CO functionalized tip. DFT calculations revealed that the multiple-step reaction, being endergonic overall, is facilitated by temporal charging and discharging of the molecule placed in the nanometric junction between the Cu tip and the Cu substrate underneath the ultra-thin NaCl film. This local probe reaction expands possibilities to synthesize nanocarbon materials in a bottom-up manner.